A Corpus Stylistic Analysis of Ernest Hemingway’s Monologues in The Old Man and the Sea - Khazraji, Abdul Baki Abdul Salam Al; Nasrallah, Mahdi Hassan (International Journal of Psychosocial Rehabilitation, 2020)
This study goes for a corpus stylistic analysis of Ernest Hemingway’s The Old Man and the Sea. Corpus-based approaches have got momentum nowadays and are being used by researchers to investigate and identify some specific phenomena in a literary text previously elusive. This study offers a systematic analysis of the language that characterizes monologues. The text of the novel is converted into plain text so corpus tool may process the data, we have analyzed the data with AntConc 3.5.8 (Anthony 2010). The findings indicate that monologues in general are characterized by the following linguistic features: pronouns related to mental state and body; linking adverbials and pronouns of the first person.